2010
DOI: 10.1115/1.4000853
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Periprosthetic Pelvis Defects With Porous Metal Implants: A Finite Element Study

Abstract: Periacetabular osteolysis is a potentially difficult surgical challenge, which can often drive the choice of reconstruction methods used in revision hip replacement. For smaller defects, impaction of bone grafts may be sufficient, but larger defects can require filler materials that provide structural support in addition to filling a void. This study utilized finite element analysis (FEA) to examine the state of stress in periprosthetic pelvic bone when subjected to a stair-climbing load and in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…According to the Paprosky classification system, the superior aspect of the acetabulum comprises an important part of the bone defect pattern. Biomechanical studies have revealed that the superior bone serves as the major support structure for acetabular cups and an essential component in the process of transmitting load from the hip to the sacroiliac joint [12,19,23], and superior and lateral migration of the COR significantly increases joint reaction force, risk of loosening, and decreased range of motion [4,17,18,21,24,35,37]. In knee revision procedures, Haddad et al proposed the concept of zone fixation in the metaphysis and diaphysis, while preserving the knee joint line level [12,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Paprosky classification system, the superior aspect of the acetabulum comprises an important part of the bone defect pattern. Biomechanical studies have revealed that the superior bone serves as the major support structure for acetabular cups and an essential component in the process of transmitting load from the hip to the sacroiliac joint [12,19,23], and superior and lateral migration of the COR significantly increases joint reaction force, risk of loosening, and decreased range of motion [4,17,18,21,24,35,37]. In knee revision procedures, Haddad et al proposed the concept of zone fixation in the metaphysis and diaphysis, while preserving the knee joint line level [12,22].…”
Section: Discussionmentioning
confidence: 99%
“…Any discrepancies between the two surgeons were re-examined by the senior consultant surgeon (YXZ). There were 13 (40.6%) patients classified as Paprosky type 3A, 19 (59.4%) as type 3B. Five (15.6%) of the type 3B patients were assessed to have pelvic discontinuity.…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…This kind of technique has been safely applied in some prosthesis revision systems [25,26]. The interfaces between the tibial tray and 3D-printed Ti-alloy were filled by bone cement, reducing the chance of fatigue and corrosion.…”
Section: Discussionmentioning
confidence: 99%
“…Finite element (FE) analysis, which can accommodate large inter-subject variations in bone geometry and material properties, has been widely used to analyse pelvic biomechanics [15][16][17][18][19]. An empirically validated FE model can provide information on the static and dynamic responses of joint structures under a variety of loading and boundary conditions that would be difficult or impossible to obtain experimentally [20][21][22].…”
Section: Introductionmentioning
confidence: 99%